Promoting structured participation for competitiveness in services companies - Jesús García-Arca; J. Carlos Prado-Prado; Arturo J. Fernández-González (Journal of Industrial Engineering and Management (JIEM), 2018)
Purpose: To identify the main drivers that facilitate the successful deployment of a participation program aimed at improving competitiveness, as a prior step to analyze and discuss the implementation of these drivers in three services companies. Design/methodology/approach: The selection of the drivers was based on a "content analysis" of recent literature (2007-2017). To test the level of deployment of these drivers, the "case study" technique was chosen. The authors have selected two public transport companies and one bank, which have more than twenty years' experience in the development of participation programs. Findings: From the case studies analysis, we conclude that participation can successfully improve a company's competitiveness, provided that the drivers are developed with this specific aim. Thus, the analysis of these drivers allows to identify some gaps in aspects such as, the extension of participation throughout the company, the methodology adopted in the deployment of participation programs, the organizational structure for monitoring the program tasks, the reward/recognition systems and, especially, the implementation of KPIs for connecting participation and competitiveness. Research limitations/implications: This paper is based on a review of current literature, the analysis of three case studies, and our own personal experience. Our observations and comments may be qualified by future investigation with an increased sample of companies. Practical implications: This paper could be of interest to companies due to outlines the drivers that are critical to implementing participation programs focused on competitiveness. This could help companies that are thinking of implementing such programs, or those that are unhappy with their current programs, to re-design their plans in line with their business strategy. Originality/value: The main contribution of this paper lies in its theoretical and applied approach, analyzing in a comparative and longitudinal way the deployment of the drivers in services companies. This analysis allows the identification of strengths and weaknesses in the implementation of these participation programs focused on competitiveness. This combined and comparative approach is considered especially novel in the academic and professional world. Likewise, the analysis of companies with a longstanding history in their participation programs is also relevant, particularly, in the services sector.
Keywords: 650; participation; continuous improvement; services companies